Dossier II: Criminología mediática: Una aproximación a sus efectos psicosociales - Herrera Rodríguez, Jacobo (Quadernos de criminología, 2022)
An approach to media criminology is exposed, specifically its conceptualization, as well as the effects it generates. The work was based on a documentary review. The review made it possible to see that there are reinforcing consequences that establish media criminology, likewise, the mass media practice actions that displace formal criminology, contributing to making crimes invisible and creating punitive populist ideas. It is also appreciated that media criminology can trigger social polarization